(3GddeY aj abg Cgd GdHjJ Ydjge GdSdGes - (3Ydj Hf GdMSjf Hf jMji Hf GdMSjf GdRjOj,J (B660 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdfcGM s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA HGH GdSde , ef cJGH GdHjhY , hBNQ eG ajg (B: (3hPcQ V jhSa QMeg Gddg Cf ePgHg bOS Gddg ai gPg Gd eSCdI , cePgH Cgd s
(3cJHJ HQSe NRGfI CejQ GdeDefjf Ydi Hf GdbGSe Hf LYaQ GdbGSeis
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3Gdabg GdESdGejs